2014
DOI: 10.17221/56/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous salicylic acid on some physiological parameters and alleviation of drought stress in Nigella sativa plant under hydroponic culture

Abstract: To study the effect of salicylic acid on photosynthetic pigments (chlorophyll a, b, total chlorophyll, and carotenoids), polyphenol compounds, anthocyanin, flavonoids, phenylalanine ammonia-lyase activity, malondialdehyde, lipoxygenase activity, electrolyte leakage, relative water content, soluble sugar contents, and protein content of black cumin (Nigella sativa) under drought stress in hydroponic culture, an experiment was conducted as a completely randomised design in a factorial arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 36 publications
9
39
0
2
Order By: Relevance
“…According to a study, under the drought stress condition flavonoids largely accumulate in the proximity of ROS generation centers and maintain the plant homeostasis. It was reported that phenolic and flavonoid content was increased in root and shoot during drought condition in Dracocephalum moldavica L. (Halimeh et al, 2013 ) and phenol content was decreased in nigella plant ( Kabiri et al, 2014). In the present research, flavanoid content increased in seedling stage many folds compared to its accumulation in vegetative stage under drought stress suggesting that seedling stage is better equipped to scavenge ROS that are generated during drought conditions.…”
Section: Discussionsupporting
confidence: 47%
“…According to a study, under the drought stress condition flavonoids largely accumulate in the proximity of ROS generation centers and maintain the plant homeostasis. It was reported that phenolic and flavonoid content was increased in root and shoot during drought condition in Dracocephalum moldavica L. (Halimeh et al, 2013 ) and phenol content was decreased in nigella plant ( Kabiri et al, 2014). In the present research, flavanoid content increased in seedling stage many folds compared to its accumulation in vegetative stage under drought stress suggesting that seedling stage is better equipped to scavenge ROS that are generated during drought conditions.…”
Section: Discussionsupporting
confidence: 47%
“…Generally, our results showed that combination of SA with PEG has improved phenolic compounds production and two key enzymes of phenolic biosynthesis pathway. Kabiri et al (2014) reported that SA increased total phenol, anthocyanin, and flavonoid content under drought stress and drought damages were reduced. In fact SA could induce activity of PAL and TAL activity and consequently phenolic compounds were increased (Bandurska and Cie´slak, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…The results in our study are in agreement with those reported by other authors. It is known that exogenous SA application enhanced the growth and photosynthetic pigments in several plant species treated under water stress such as wheat (Singh and Usha, 2003), Nigella sativa (Kabiri et al, 2014), Zoysiagrass (Chen et al, 2014), mustard (Nazar et al, 2015). Increase in fresh and dry mass by SA application under drought stress can be related to the positive effect of SA on photosynthetic pigments which led to the improvement in growth.…”
Section: Resultsmentioning
confidence: 99%
“…Salicylic acid, a natural phenolic compound and a signaling molecule with ubiquitous distribution in plants, is found in many plant tissues . This compound is considered as a plant hormone .…”
Section: Introductionmentioning
confidence: 99%
“…This compound is considered as a plant hormone . It plays a vital role in crucial physiological processes of plants such as stress resistance and systemic acquired resistance (SAR) in different plant organs . It also plays critical roles in plants including respiration, stomatal movement, photomorphogenesis, seed germination, cell growth, and senescence .…”
Section: Introductionmentioning
confidence: 99%